A novel free-hanging 3D printing method for continuous carbon fiber reinforced thermoplastic lattice truss core structures. (5th January 2018) - Liu, Shuting; Li, Yingguang; Li, Nanya
Abstract: Continuous Fiber Reinforced Thermoplastic (CFRTP) lattice truss core structures are potential to aerospace engineering because of their high weight reduction efficiency and multifunctional application. A novel free-hanging 3D printing method was firstly presented by the authors to manufacture CFRTP lattice truss core structures. The free-hanging printing path generation strategy was established to realize the undercut and overhanging truss structure without any support. Based on the free-hanging 3D printing method, the typical lattice topologies and more complex structures like the integral variable-thickness wing were printed. The cross sectional morphology of samples printed by using the free-hanging printing method were analyzed. The investigations on the parameters such as relative density, fiber volume content and truss angle were conducted to reveal the relationship between the process parameters and out-of-plane compressive properties. The experiment results demonstrated that the average structural error was about 1.89% compared with the theoretical geometry. The compression strength of the printed sample was 224% higher than that of the pure thermoplastic resin counterpart. The specific compressive strength of free-hanging printed samples was in competitive status compared with currently existed CFRTP lattice structures in available literatures. Graphical abstract: Highlights: A free-hanging 3D printing method was proposed for processing continuous fiber reinforced thermoplastic lattice structures. The printing path generation strategy was established based on the relations between printing constraints and parameters. The lattice structures with different topological features including the integral variable-thickness wing were printed. Experimental investigations were conducted to evaluate the printing accuracy and quality.